Technical feasibility of EUS‐guided antegrade dilation for hepaticojejunostomy anastomotic stricture using novel endoscopic device (with videos). Issue 3 (1st April 2019) - Ueshima, Kazuya; Ogura, Takeshi; Nishioka, Nobu; Miyano, Akira; Okuda, Atsushi; Imanishi, Miyuki; Higuchi, Kazuhide
Abstract : Background: A novel endoscopic dilation device (EZ Dilator; Zeon Medical Co, Tokyo, Japan) is now available in Japan that might affect dilation for biliary strictures under endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS) guidance because it has good push ability. We evaluated the technical feasibility of this device under EUS guidance in a case series of patients with hepaticojejunostomy anastomotic stricture (HJAS) that led to further complications. Method: We enrolled 14 patients with HJAS leading to obstructive jaundice or repeated cholangitis in this study. Technical success was defined as insertion of the EZ Dilator into the intestine across the stricture site without the need for other dilation devices. Deployed plastic stents were removed after three months to evaluate anastomosis sites. Results: The median procedural duration was 25 minutes. Rates of technical and clinical success were 100% and 78.5%, respectively. One patient developed an adverse event of abdominal pain. Contrast medium flowed across the anastomosis site in 11 patients after stent removal, indicating a clinical success rate of 78.5% (11 of 14). Plastic stents were deployed again in the remaining three patients. Conclusion: Although a prospective evaluation with long‐term follow up is needed, the EZ Dilator shows clinical promise for treating benign biliary strictures under ERCP and EUS guidance.